Evaluation of a New Agent for Wettability Alteration During Enhanced Oil Recovery - Ghassem Zargar; Mohammad Ali Takassi; Siamak Moradi; Ali Reza Rostami; Babak Jabari (Iranian Journal of Chemistry & Chemical Engineering, 2020)
Wettability alteration is an important mechanism when applying surfactants during enhanced oil recovery (EOR). Moreover, in carbonate reservoirs, the rock has more tendencies to be oil-wet than those of sandstone reservoirs. This mainly arises from the interaction amongst the carbonate surface chemistry exposed to the asphaltenic/aromatic components of crude oil. Therefore, it is of great significance to develop surfactants with high efficiency in wettability alteration of carbonate rocks. In this work, a cationic surfactant n-dodecyl trimethylammonium bromide (DTEAB), was prepared and applied in a wettability alteration experiment for the first time. Then, the critical micelle concentration and wettability properties were studied by means of electrical conductivity and sessile drop techniques, respectively. Consequently, it was observed that this surfactant can alter the wettability of Bangestan rock pellets from oil-wet to water-wet state, and the results are better than that of wettability alteration observed for Khark rock pellets. Based on this mechanism, nearby 22% Original Oil in Place (OOIP) was obtained by tertiary surfactant flood during core displacement in excess of ultimate recovery factor of secondary water injection. As a consequence, the suggested cationic surfactant in this study can be a good agent for increasing the oil recovery factors in the petroleum industry.